MEDIA INTERAKTIF WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR AKSARA BALI - Dwi Swasmini, Ni Kadek; Putu Purnami, Ida Ayu; Putra Manik Aryana, Ida Bagus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the use of interactive wordwall media in increasing student learning motivation. This study uses a pre-experimental design research method with a one-group pre-test-post-test design research design. Data collection in this study uses observation sheets of student learning motivation before and after using interactive wordwall media and using tests in the form of pre-test and post-test. Data analysis techniques used in this study are descriptive qualitative and descriptive quantitative techniques. The results obtained from observations of student learning motivation before using interactive wordwall media obtained a percentage of 56.67% which is included in the medium category and after using interactive wordwall media obtained a percentage of 96.67% which is included in the high category. There is an increase in student learning motivation by 40%. The results of the tests in the form of pre-test and post-test show that the average value in the pre-test is 60 while in the post-test obtained an average value of 86.11.